Challenges and Prospects of ‘ICT’ in Socio-Economic Growth in Higher Learning Institutions of India - Dr Pavan Kumar Gupta (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The application of Information and Communication Technologies (ICTs) is already changing the organization and delivery of higher education. The pedagogical and socio-economic forces that have driven the higher learning institutions to adopt and incorporate ICTs in teaching and learning include greater information access; greater communication; synchronous and asynchronous learning; increased cooperation and collaboration, cost-effectiveness and pedagogical improvement. However, ICTs have not permeated to a great extent in many higher learning institutions in most developing countries due to many socio-economic and technological circumstances. This paper discusses new learning and training technologies considering their pedagogical, cost and technical implications. It also discusses challenges for integrating these technologies in higher learning institutions with examples from India, and giving best practice approaches for addressing each of the challenges.